2021
DOI: 10.1016/j.ssmph.2021.100797
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study on mortality among Belgian immigrants during the first COVID-19 wave in Belgium. Can demographic and socioeconomic indicators explain differential mortality?

Abstract: Introduction Belgium has noted a significant excess mortality during the first COVID-19 wave. Research in other countries has shown that people with migrant origin are disproportionally affected. Belgium has an ethnically diverse and increasingly ageing population and is therefore particularly apt to study differential mortality by migrant group during this first wave of COVID-19. Data and methods We used nationwide individually-linked data from the Belgian National Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 25 publications
5
35
0
Order By: Relevance
“…However, the use of PAFs provides us with an uncomplicated inequality measure. It is translatable to policy measures by addressing the population impact of inequalities in area deprivation and the potential gain by instating policy measures that aim to reduce these inequalities [ 15 ]. Our results demonstrate that the PAFs can present a useful instrument to gain insights into the relative burden of living in a deprived area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of PAFs provides us with an uncomplicated inequality measure. It is translatable to policy measures by addressing the population impact of inequalities in area deprivation and the potential gain by instating policy measures that aim to reduce these inequalities [ 15 ]. Our results demonstrate that the PAFs can present a useful instrument to gain insights into the relative burden of living in a deprived area.…”
Section: Discussionmentioning
confidence: 99%
“…Our results provide valuable insights into spatio-temporal patterns of SE inequalities in COVID-19 incidence in Belgium. The large majority of studies on COVID-19 and SE differences in Belgium are based on excess mortality and these studies indicate the existence of SE inequalities during the first Belgian COVID-19 epidemiological wave [ 13 , 15 – 17 ]. Our study is the first in Belgium that focusses on SE inequalities in COVID-19 cases over a larger period of time, also taking into account a temporal gradient.…”
Section: Discussionmentioning
confidence: 99%
“…These studies found that mortality increased, most notably among socioeconomically disadvantaged groups (Drefahl et al, 2020), people living in crowded and multigenerational households (Brandén et al, 2020) and migrants (Aradhya et al, 2021;Rostila et al, 2021). Similar studies on mortality among foreign-born populations have been conducted in Norway (Indseth et al, 2020) and Belgium (Vanthomme et al, 2021). Calderón-Larrañaga et al (2020) showed that mortality in Stockholm was elevated in areas with lower incomes and/or in areas with more foreign-born residents.…”
Section: Introductionsupporting
confidence: 57%
“…With more than 8800 additional deaths during the first wave, Belgium had a high COVID-19 related excess mortality. Elderly male immigrants had higher mortality rates in 2020 than natives compared to the previous year, with striking excess mortality rates for SSA women and men at middle age (40 and 70% increase respectively), typically related to their socio-economic and demographic position [ 28 ].…”
Section: Introductionmentioning
confidence: 99%